Experimental Study on Thermal Expansion Behavior of Concrete under Three-Dimensional Stress - Zhipeng Yu; Fan Zhang; Xiao Ma; Fujian Yang; Dawei Hu; Hui Zhou (Advances in Civil Engineering)
Concrete is widely used in underground engineering and bears three-dimensional stress transmitted by overlying load. When a fire occurs, the thermal expansion of concrete structure under such stress state is different from that under stress-free state. For this purpose, a self-developed real-time high-temperature true triaxial test system was applied to investigate the thermal expansion behavior of concrete under three-dimensional stress state. The thermal expansion strain of concrete under the three-dimensional stress undergoes strain increasing and strain stabilizing stages. At 600°C, the maximum thermal expansion strain of concrete under the three-dimensional stress is 0.75%. The average coefficient of thermal expansion of concrete under three-dimensional stress condition was then calculated, and its value reaches the minimum of 8.68 × 10−6/°C at 200°C and the maximum of 13.41 × 10−6/°C at 500°C. Comparing the coefficient of thermal expansion of concrete under stress-free condition given by Eurocode, it is found that the three-dimensional stress has an obvious restraint on the thermal expansion of concrete. The research results can provide theoretical basis for the stability analysis of underground engineering concrete structures under high-temperature environment.